Dampak Pariwisata terhadap Aspek Sosial Budaya Masyarakat Desa Adat Kemiren di Kabupaten Banyuwangi - Wahyudiono, Andhika; Imaniar, Dimas (representamen, 2021)
Cultural tourism is the main attraction in the traditional village of Kemiren, Banyuwangi Regency. Macananegara tourists as well as domestic tourists visit the traditional village of Kemiren to witness first-hand the life of the Osing tribe which is still traditional. This research was conducted to determine the impact of tourism on the socio-cultural aspects of the people of the Kemiren traditional village, Banyuwangi Regency. This research is a qualitative research. Meanwhile, the strategy carried out by the government is in the form of preventive actions such as outreach to MSME players, making local regulations on tourism and study tours of tourism management with tourism business actors. The basic conclusion in this study later is, as a cultural tourism destination in general, the ongoing tourism industry activities affect the socio-cultural aspects of the Osing community, the Kemiren traditional village, Banyuwangi Regency. In addition, the increase in the community's economy is also encouraged due to changes in the livelihoods of local residents, as well as local government strategies in the form of policy making are expected to be able to minimize the negative impact of tourism. Cultural tourism in the traditional village of Kemiren, Banyuwangi Regency is used as a tool to maintain the cultural existence of the Kemiren traditional village, which is currently being abandoned by the Osing tribe, the traditional village of Kemiren, Banyuwangi Regency.Keywords: Tourism, Socio-culture, Osing Tribe